CRYPTOCURRENCY TRANSACTION: IS IT RELEVANT TO INDONESIAN ACCOUNTING STANDARDS? - Nadiar, Rahmi; Nor, Wahyudin; Safrida, Lili (Universitas Muhammadiyah Surakarta, 2022)
Background: There are no specific accounting standards that may relevant to cryptocurrency transactions. It leads to dissimilar accounting treatments for numerous entities. Based on the existing issues and regulations in Indonesia, how is the classification of accounts possibly relevant to the Indonesian accounting standards? Purpose and Methods: This study attempted to explain and analyse the accounting challenges for cryptocurrencies within the current accounting framework in Indonesia and identify relevant models for cryptocurrency accounting. This study is qualitative. Data sources used in this study included key informant interviews. Findings: The study findings concluded that there are deficiencies in the Indonesian accounting standards. It is driven by differences in the use of an entity’s business model. Differences in business activity lead to differing uses in cryptocurrency accounting. Research Limitation: The results of the research depend on the author’s experience and perspective. The scope of topics can be expanded by adding additional perspectives. Contribution: This study can contribute to developing the accounting standards in Indonesia. The growing popularity of cryptocurrencies has indirectly led regulators to design new guidance for accounting financial statements.